Conservation tillage and preceding rainy-season crops on root: shoot characteristics, productivity, profitability and nutrient uptake of succeeding mustard under semi-arid rainfed ecosystem - Amgain, Lal Prasad; Sharma, Ajit Ram (Journal of Agriculture and Natural Resources, 2021)
Conservation tillage practices are poplar, environmental friendly and economically feasible approaches to increase the productivity and resource-use efficiency of arid and semi-arid rainfed ecosystems. Rainfed field experiments were accomplished at IARI, Pusa, New Delhi in 2010-11 and 2011-12 to evaluate root: shoot growth, productivity, profitability and nutrient uptake in mustard under the various conservation tillage practices with preceding rainy- season crops; pearlmillet, clusterbean and greengram; and organic mulches, viz. no residues, crop residues and Leucaena twigs applied to both rainy- season crops and mustard grown with common recommended package of practices. Higher root length density (RLD), root surface area (RSA), root volume density (RVD), average root diameter (RD), crop growth rate (CGR), relative growth rate (RGR) and net assimilation rate (NAR) were recorded under clusterbean–mustard and greengram–mustard systems over the pearlmillet- mustard system. Interaction between crop residues and preceding rainy-season crops on growth parameters exerted significant variations, while yield attributes showed the mixed responses. Mustard seed yield was significantly higher (+51%) in 2010-11 (1.80 t ha-1) than that of 2011-12 (1.19 t ha-1). Economic analysis exhibited the highest returns and net returns/ Rs invested after clusterbean with Leucaena twigs mulching. The nutrient uptake followed the same trend as that of seed and stalk yield. It was concluded that growing mustard after clusterbean with Leucaena twigs mulching was high-yielding and profitable cropping system under conservation tilled semi-arid rainfed ecosystem.